2008
DOI: 10.1111/j.1540-8191.2007.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen-Slice Multidetector Computed Tomography for Graft Patency Evaluation After Coronary Artery Bypass Surgery

Abstract: Sixteen-slice MDCT allows for noninvasive evaluation of coronary bypass grafts patency with high diagnostic accuracy. Assessment of distal anastomotic stenosis was deficient, particularly for arterial grafts, still limited by low resolution or artifacts. Improved accuracy may be obtained by more aggressive heart rate reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The overall sensitivity and specificity of MDCT angiography for the detection of graft patency were 87% and 97%, respectively. Although the sensitivity was somewhat low (but acceptable), the specificity, PPV (94%), and NPV (93%) were comparable with the results of other studies that used 16-slice systems [Yamamoto 2006;Houslay 2007;Uva 2008;von Kiedrowski 2009]. The largest study thus far, which was conducted with 64-slice MDCT angiography in 138 patients, reported sensitivity and specificity values of 97% each for the evaluation of bypass graft occlusion and stenosis [Meyer 2007].…”
Section: Discussionsupporting
confidence: 68%
“…The overall sensitivity and specificity of MDCT angiography for the detection of graft patency were 87% and 97%, respectively. Although the sensitivity was somewhat low (but acceptable), the specificity, PPV (94%), and NPV (93%) were comparable with the results of other studies that used 16-slice systems [Yamamoto 2006;Houslay 2007;Uva 2008;von Kiedrowski 2009]. The largest study thus far, which was conducted with 64-slice MDCT angiography in 138 patients, reported sensitivity and specificity values of 97% each for the evaluation of bypass graft occlusion and stenosis [Meyer 2007].…”
Section: Discussionsupporting
confidence: 68%
“…Sudden deaths can also occur in patients undergoing cardiovascular surgery. MDCT angiography allows for the non-invasive evaluation of coronary bypass graft patency with a high diagnostic accuracy [53,54]. MDCTA is a reliable non-invasive diagnostic method that can clearly display the stent lumen and is especially helpful for patient follow-up.…”
Section: Sudden Postoperative Deathsmentioning
confidence: 99%
“…Only 62% to 74% of grafts were evaluable, and sensitivities and specifi cities were between 95% and 100% for the assessment of graft patency. Sensitivities and specifi cities were between 80% and 96% for the detection of signifi cant graft stenosis [7,[19][20][21][22][23][24][25][26][27][28][29]. In case of graft patency, detection of de novo lesions in nongrafted coronary arteries and coronary segments located proximal to the distal graft anastomosis may be of therapeutic relevance for interventional or surgical planning.…”
Section: Historical Perspectivementioning
confidence: 98%